2011
DOI: 10.1002/pmic.201000698
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and proteomic characterization ofStaphylococcus aureusmastitis isolates of bovine origin

Abstract: Staphylococcus aureus colonizes and infects humans as well as animals. In the present study, 17 S. aureus strains isolated from cows suffering from mastitis were characterized. The well-established multilocus sequence typing (MLST) technique and a diagnostic microarray covering 185 S. aureus virulence and resistance genes were used for genetic and epidemiological analyses. Virulence gene expression studies were performed by analyzing the extracellular protein pattern of each isolate on 2-D gels. By this way, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…It was demonstrated that this subtype differed from avirulent strains in more that 400 ORFs [46]. Similarly, a proteomic approach indicated that multiple factors are involved in human and bovine host specificity [47]. In the present study the chicken embryo model clearly clustered poultry strains into virulent (ch3, ch5, ch8, ch9, ch21, ch23, ch25, and pa2), avirulent (ch22, ch24, pa3, ph1, ph2, and t2), and intermediate groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was demonstrated that this subtype differed from avirulent strains in more that 400 ORFs [46]. Similarly, a proteomic approach indicated that multiple factors are involved in human and bovine host specificity [47]. In the present study the chicken embryo model clearly clustered poultry strains into virulent (ch3, ch5, ch8, ch9, ch21, ch23, ch25, and pa2), avirulent (ch22, ch24, pa3, ph1, ph2, and t2), and intermediate groups.…”
Section: Discussionmentioning
confidence: 91%
“…As Triplex PCR is based on co-amplification of fragments of spa, coa, and the hypervariable region adjacent to mecA [35], allelic variation in one of these regions may explain the unusual virulence of this strain. Another explanation is that despite close genetic relatedness, the exoproteome composition of ch21 and ch22 may vary significantly because of variability in gene expression [47,48]. These possibilities are currently being evaluated to identify the factors responsible for the observed differences in virulence of those two strains.…”
Section: Discussionmentioning
confidence: 95%
“…The majority of these strains belongs to CC97 (47.5%) and CC151 (47.5%). Other studies showed that the latter CCs are distributed worldwide and constitute the major groups causing mastitis infection outbreaks, mainly in North and South America and Europe [50], [51]. However, CC126 is most predominant in Brazil, along with CC97 [52].…”
Section: Resultsmentioning
confidence: 99%
“…b Originally isolated from clinical or sub-clinical cases of mastitis, cf ref. 65; c was shown to cause transient or persistent infection of udder cells, cf ref. 44.…”
Section: Resultsmentioning
confidence: 99%
“…That S . aureus strain has in addition been characterized at the genomic and proteomic level 65 together with the S . aureus strains RF122 (originally isolated from clinical mastitis), B and D. The latter two strains had been isolated from subclinical cases of mastitis.…”
Section: Methodsmentioning
confidence: 99%